Fitzgerald’s Critiques on American Capitalism in His “The Great Gatsby” - Tsamratul’aeni Tsamratul’aeni (Universitas Cokroaminoto Palopo, 2016)
The research aims to describe Fitzgerald’s criticism presented through the novel, and to identify the capitalism concept portrayed in the novel. The research reveals the existence of the capitalism in the form of literary work. Method in the research is the qualitative descriptive method with the literary sociological approach. Data in the research are the characters and narrator’s expressions performed and uttered throughout the work. The expression are situated in several fragments in the work and they are analyzed continually. The research result indicates that capitalism is portrayed through the attitudes of the charachters in the novel. They represents the materialism and capitalism which has certainly created the gaps in the social life by indicating the different places of the West Egg and East Egg. The other gap is the different status that the characters belong to. The capitalism is repeatable in our current life because morally the community nowadays has also been corrupted as has been presented in newspapers everyday, as the examples murder, rape, divorce, and abuse. Moral decadence is the result of lack of spiritual values, the impact of money or materialism, lack of performing religious duties, and like violating the social rules.